The Design of a Information System of Student Attandance Recording with RESTful Web Service Architecture in SMK Batik 2 Surakarta - Hilda Debora; Dwi Maryono; Rosihan Ari Yuana (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2019)
The student attendance is one of the important aspects of the education process to assess the level of discipline of students and be an indicator of whether students need specific guidance related to the attendance. This research aims to design a web-based information system with RESTful web service architecture to help teachers activities for checking student attendance and recapitulation of data recording with more easily. This research uses the methods of research and development (R&D) and implemented at SMK 2 Batik Surakarta. System development method that used in the information system is Waterfall Model. The steps of Waterfall Model consist of analysis, design, code, and test. The end result of this research is the feasibility of the system based on the results of testing on the aspects of functionality yielded a value of 1 (good) while on the aspects of usability obtained percentage amounting to 81.47% (very high), so it can be inferred that This system is worth to use.